Clinical management of chlamydia in general practice: A survey of reported practice. Issue 3 (1st July 2002) - Griffiths, Catherine; Cuddigan, Astrid
Abstract : Background: Chlamydia trachomatis is the most common curable sexually transmitted infection (STI) in the UK. Prevalence of the infection in different health care settings has been found to be between 2% and 29% and diagnoses of the infection continue to rise significantly. It is estimated, however, that only 10% of all chlamydial infections are seen and treated in genitourinary medicine (GUM) clinics. Few data exist about the actual practice patterns of primary care providers in the management of chlamydia. The management of patients identified with the infection within this setting warrants attention. Aims: To determine general practitioners' (GPs') and nurses' reported clinical practice in the management of genital chlamydial infection. To design a needs-based education guideline on the management of chlamydia in rural primary care. Design: An anonymous, confidential, self-administered postal questionnaire was sent to all GPs and cervical cytology practice nurses in 84 practices in Dyfed Powys Health Authority (DPHA) area, Wales, UK. Results: Following two mailings of the survey, responses were obtained from 75/84 practices (response rate 89%). A total of 130/307 GPs (response rate 42%) and 72/152 nurses (response rate 47%) in these practices responded. The data demonstrated that few tests for chlamydia are being carried out in general practice: 42% (55/130) of GPs and 54% (37/72) of nurses reported carrying out between one and four tests a month, and 35% (46/130) of GPs and 29% (21/72) of nurses reported performing less than one test a month. Very few positive results are being obtained. The majority of GPs (72%) and nurses (68%) routinely use the appropriate endocervical swab when testing for chlamydia, however 19% of GPs and 20% of nurses are using either an incorrect wooden-stemmed swab or are taking an inappropriate high vaginal swab. Conclusions: Few chlamydia tests are being performed in primary care in DPHA, Wales. Health professionals in general practice are in need of, and are in favour of, up-to-date training on all aspects of chlamydial identification and management in primary care. Attention needs to be focused upon resources and the paucity of GUM services and their access within the DPHA area.